Manejo de irrigação para cultivares de palma de óleo (Elaeis guineensis Jacq.) em fase inicial de desenvolvimento no norte de Mato Grosso - Cazarin Júnior, Airton (2014)
In Brazil, among the vegetable oils used in biodiesel production, oil palm has grest potential, standinpas an option to petroleum diesel and contributing to the creation of a market for large-scale production of biodiesel. Besides occupying a prominent position in the production and generation of renewable energy from agricultural sources, the Brazil has extensive agricultural areas that can be incorporated into the production process in a sustainable manner. Palm oil is currently the world's largest oilseed productivity, presenting oil yield of 3 to 6 tons per hectare annually. It has a good adaptive capacity and is a great alternative for restoration of degraded areas. According to the Agro-Ecological Zoning of Oil Palm, the northern state of Mato Grosso is considered as a regular and marginal area, with restrictions on water deficit ranging from 200 to 450 mm year. In this context the goal of this study was to evaluate the initial development of two oil palm cultivars under irrigated and rainfed system, in Sinop - MT, to establish a the best strategy for irrigation management. The experimental randomized block was designed with two cultivars (BRS C2501 and BRS C2528), and four soil water depletion levels (10, 20, 30 and 40% of the total available water in the soil) as well as a rainfed conditions, all with three replications (blocks). Each experimental plot consisted of five plants, that were evaluated on monthly basis regarding their morphological characteristics: canopy average diameter (DMP), number of leaves (NL) and width of leaves (LF). Therefore, it took two experiments. In the first we used a randomized blocks, with two cultivars (BRS C2501 and C2528 BRS) and four levels of water depletion in the soil (10, 20, 30 and 40% of the total soil water availability), all with three replications (blocks). In the second we used a randomized blocks, with two cultivars (BRS C2501 and C2528 BRS) and both systems (rainfed and irrigated), all with three replications (blocks). Each plot consisted of five plants, which were evaluated monthly: average diameter of crown projection (DMP), number of leaves (NF) and width of leaves (LF). The data were analyzed in three periods (1 rainy, dry and rainy 2), and compared the two cultivars, depletion levels and development in both systems (irrigated and viii rainfed). When significantly different, the means were submitted to comparison by Tukey test or regression, where a 5% probability. It was concluded that the BRS C2501 and C2528 BRS cultivars showed similar vegetative growth and the irrigation system was higher than non-irrigated.